2016
DOI: 10.1080/16070658.2016.1219468
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing of vitamin products by retail pharmacies in South Africa: Implications for dietitians

Abstract: Objective: The objective of this study was to analyse the dispensing patterns of vitamins (Anatomical Therapeutic Chemical (ATC) group A11) over a one-year period in a group of community pharmacies in South Africa. Design and setting: A retrospective drug utilisation study was conducted on community pharmacy electronic dispensing records in South Africa recorded in 2013. Outcome measures: All products for ATC subgroup A11 were extracted and analysed. Results: A total of 164 233 vitamin products were dispensed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A previous study on the dispensing of vitamins by retail/community pharmacies in South Africa found that ergocalciferol (Anatomic Therapeutic Chemical (ATC) classification code A11CC01), which is available only on prescription, was the most often dispensed (37.48%) of all prescription vitamin products in 2013. 32,44 Public health prescribing is more difficult to ascertain, as public hospitals and community health centres and clinics do not utilise retail/community pharmacies, medication is given free of charge by the facility and electronic records are not nationally linked; however, there is a tendency for the private healthcare sector to lead the way in the prescribing of nutraceuticals. Establishing private healthcare prescribing patterns may provide an indication of the trend in prescribing of vitamin D and, consequently, the possible future public healthcare prescribing, expenditure and the cost-benefit ratio of vitamin D supplementation on a broader scale.…”
Section: Prescribing Of Vitamin D In South Africamentioning
confidence: 99%
“…A previous study on the dispensing of vitamins by retail/community pharmacies in South Africa found that ergocalciferol (Anatomic Therapeutic Chemical (ATC) classification code A11CC01), which is available only on prescription, was the most often dispensed (37.48%) of all prescription vitamin products in 2013. 32,44 Public health prescribing is more difficult to ascertain, as public hospitals and community health centres and clinics do not utilise retail/community pharmacies, medication is given free of charge by the facility and electronic records are not nationally linked; however, there is a tendency for the private healthcare sector to lead the way in the prescribing of nutraceuticals. Establishing private healthcare prescribing patterns may provide an indication of the trend in prescribing of vitamin D and, consequently, the possible future public healthcare prescribing, expenditure and the cost-benefit ratio of vitamin D supplementation on a broader scale.…”
Section: Prescribing Of Vitamin D In South Africamentioning
confidence: 99%